Embryonic developmental study on inner ear of Columba livia domestica (the early, intermediate stages) - El-Balshy, Ragaa; Si, Abd El-Hady; M M, El-Hady; Sh, El-Sayed (International Journal of Biological Research, 2014)
The present study deals with the embryonic development of the early and the intermediate embryonic stages of Columba livia domestica inner ear or the membranous labyrinth (10, 15, 20, 22, 26,30,33,36 and 47 mm total body length). During the early development (10 mm stage), neuroepithelium of the ventral rhompencephalon evaginates laterally to form an ectoderm thickening, the otic placode. The latter invaginates forming the otocyst that subsequently gives all other components of the membranous labyrinth. The surrounding mesenchyme is the origin of cartilaginous capsule of the ear. The endolymphatic duct is the first appeared structure in 15 mm stage, followed by cochlear duct (in 22 mm stage) and finally the three semicircular ducts. The latter begin in 26 mm stage and end in 47 mm stage .The inner ear contains sensory organs; the macula of ( utriclus , sacculus) and the crista ampullaris ( of the three semicircular canals ) and the basilar papillae of the cochlear duct; not only for the sense of hearing but also for the equilibrium ,stability and balance. The sensory organs of the intermediate stages (36 and 47 mm stages) showed no differentiation to hair or supporting cells. In the intermediate stage (47 mm stage), the inner ear has undergone a considerable development in its structure. It consists of a dorsal vestibular part including two connecting sacs (utriculus and the sacculus) and three semicircular canals and ventral cochlear part (the cochlear duct). Keywords: Columba, Embryo, Early, Intermediate Stages, Inner Ear Development.